The risk of coronary artery disease in patients with rheumatoid arthritis using Chinese herbal products and conventional medicine in parallel: a population-based cohort study - Han-Hua Yu; Nai-Huan Hsiung; Jen-Huai Chiang; Hsuan-Shu Shen (BMC, 2020)
Abstract Background Few studies have evaluated the association between the risk of coronary artery disease (CAD) and the use of Chinese herbal products (CHP) in patients with rheumatoid arthritis (RA). This study investigated the risk of CAD among patients with RA using CHP in combination with conventional medicine. Methods A retrospective cohort study was conducted using the Taiwan National Insurance Research Database to assess 22,353 patients who had been newly diagnosed with RA between 1997 and 2010. Patients were assigned to the CHP group or non-CHP group according to their use or nonuse of CHP after being diagnosed with RA. The Cox proportional hazards model was used to estimate the hazard ratio (HR) of CAD for a 1:1 matched sample. Results Both the CHP and non-CHP groups comprised 4889 patients after 1:1 matching. The risk of CAD was significantly reduced in the CHP group [adjusted HR (aHR): 0.59, 95% confidence interval (CI): 0.50-0.71] compard with the non-CHP group. Those who used CHP for > 180 days had an even lower risk of CAD than users with CHP usage less than 30 days (aHR: 0.64, 95% CI: 0.43-0.95). Additionally, frequently prescribed formulae, such as Kuei-Chih-Shao-Yao-Chih-Mu-Tang, Tang-Kuei-Nien-Tung-Tang, and Shu-Ching-Huo-Hsieh-Tang, were associated with a reduced risk of CAD. Conclusion The use of CHP was associated with a lower risk of CAD in patients with RA. Additional randomized controlled trials are required to assess any causal relationship between the effect of CHP usage and the risk of CAD.